Remixing Persona : An Imaginary Digital Media Object from the Onto-Tales of the Digital Afterlife - Amerika, Mark; Kim, Laura (Open Humanities Press, 2019)
Remixing Persona: An Imaginary Digital Media Object from the Onto-Tales of the Digital Afterlife is comprised of two components: a visual manifesto that doubles as a theoretical e-reader and a work of music video art. In building this project, the artists collaboratively investigate persona-making, performance-thinking, and applied remixology.
English
Keywords: The arts; Digital lifestyle; Digital Media object; visual manifesto; e-reader; music video art